Implementasi Kurikulum dan Evaluasi Dalam Meningkatkan Mutu Lulusan Pada SDN Tanjung Priok 02 Jakarta - Hendra Cipto; Shantyaswari Prihandini; Hanafiah Hanafiah (Peneliti.net, 2023)
The success of a school in improving student achievement as an indicator of the quality of graduates is highly dependent on the effectiveness of its curriculum management implementation. The purpose of this research is to elaborate on curriculum implementation and evaluation in improving the quality of graduates at SDN Tanjung Priok Jakarta. The research method used is descriptive research method. The results of the study show that Curriculum Management in Improving Graduate Quality consists of four stages, namely planning, organizing, implementing, and evaluating. Curriculum planning includes determining objectives, determining methods, determining material or content, and determining evaluation. Organizing the curriculum includes preparing an academic calendar, preparing lesson schedules, setting the duties and obligations of teaching staff, and school activity programs. Implementation of the curriculum includes learning materials or materials, learning strategies and methods, learning facilities and infrastructure, and learning assessment systems. Curriculum evaluation includes evaluation of educational goals, evaluation of content or materials, evaluation of learning strategies, and evaluation of assessment programs.